NbWRKY40 Positively Regulates the Response of Nicotiana benthamiana to Tomato Mosaic Virus via Salicylic Acid Signaling - Jiang, Yaoyao; Zheng, Weiran; Li, Jing; Liu, Peng; Zhong, Kaili; Jin, Peng; Xu, Miaoze; Yang, Jian; Chen, Jianping (Frontiers in Plant Science, 2021)
WRKY transcription factors play important roles in plants, including responses to stress; however, our understanding of the function of WRKY genes in plant responses to viral infection remains limited. In this study, we investigated the role of NbWRKY40 in Nicotiana benthamiana resistance to tomato mosaic virus (ToMV). NbWRKY40 was significantly downregulated by ToMV infection, and subcellular localization analysis indicated that NbWRKY40 was targeted to the nucleus. In addition, NbWRKY40 activated W-box-dependent transcription in plants and showed transcriptional activation in yeast cells. Overexpressing NbWRKY40 (OEWRKY40) inhibited ToMV infection, whereas NbWRKY40 silencing conferred susceptibility. The level of salicylic acid (SA) was significantly higher in OEWRKY40 plants compared with that of wild-type plants. In addition, transcript levels of the SA-biosynthesis gene (ICS1) and SA-signaling genes (PR1b and PR2) were dramatically higher in OEWRKY40 plants than in the control but lower in NbWRKY40-silenced plants than in the control. Furthermore, electrophoretic mobility shift assays showed that NbWRKY40 can bind the W-box element of ICS1. Callose staining revealed that the plasmodesmata was decreased in OEWRKY40 plants but increased in NbWRKY40-silenced plants. Exogenous application of SA also reduced viral accumulation in NbWRKY40-silenced plants infected with ToMV. RT-qPCR indicated that NbWRKY40 did not affect the replication of ToMV in protoplasts. Collectively, our findings suggest that NbWRKY40 likely regulates anti-ToMV resistance by regulating the expression of SA, resulting in the deposition of callose at the neck of plasmodesmata, which inhibits viral movement.